POTENSI RIBA DALAM LEMBAGA KEUANGAN SYARIAH (LKS) DI KABUPATEN PONOROGO - Ahmad Wafa (IAIN Ponorogo, 2019)
Nowadays, in almost every transaction, it is almost impossible to avoid usury, as well as transactions in sharia financial institutions themselves. In theory it might have been very perfect and avoided usury, but in its implementation it had not been completely free from usury. Usury has plagued and penetrated almost all the joints of the Indonesian economy. This article tries to dig deeper and find small potentials that can be missed a little more. The conclusions of this study are: First, the legal contract (contract) that is used is still found in the potential to fall into usury or it can be called the back door of usury. Second, the implementation of sharia products sometimes forgets the crucial things the basic principle of the contract itself, for example the determination of margins based on the financing principal provided, not based on the buying and selling object in the murābaḥah contract. Determination of the capital principal value of 70% of the selling price of the collateral provided by the Customer and is definitely profitable. Third, the application of the LKS financing contract in Ponorogo which is not yet 100% has a direct impact on the Customer, namely a very large margin of 49.39% and the potential for usury by 19.39% of the principal capital issued by the bank on murābaḥah financing. Disbursement of muḍārabah funds is not 100% given by the Customer as capital manager and profit determination at the beginning of the contract without seeing the customer profit or loss. Dewasa ini dalam setiap transaksi hampir dapat dikatakan mustahil untuk terhindar dari riba, begitupun transaksi-transaksi dalam lembaga keuangan syariah sendiri. Secara teori mungkin telah sangat sempurna dan terhindar dari riba, namun dalam pelaksanaannya belum sepenuhnya terbebas dari riba. Riba telah menjangkiti dan merasuki hampir seluruh sendi-sendi perekonomian Indonesia. Artikel ini berusaha menggali lebih dalam dan menemukan potensi-potensi kecil yang sedikit banyak bisa terlewatkan. Kesimpulan dari kajian ini yaitu: Pertama, Legal kontrak (akad) yang digunakan masih ditemui potensi-potensi jatuh kepada riba atau bisa disebut pintu belakang dari riba. Kedua, Pelaksanaan produk syariah ini terkadang melupakan hal-hal krusial prinsip dasar dari akad itu sendiri misalnya penetapan margin berdasarkan pokok pembiayaan yang diberikan, bukan berdasarkan obyek jual beli pada akad murābaḥah. Penetapan nilai pokok modal 70 % dari harga jual agunan yang diberikan Nasabah dan pasti untung. Ketiga, Penerapan akad pembiayaan LKS di Ponorogo yang belum sesuai 100% berdampak langsung terhadap Nasabah yaitu margin yang sangat besar 49,39% dan berpotensi riba sebesar 19,39% dari modal pokok yang dikeluarkan oleh bank pada pembiayaan murābaḥah. Pencairan dana muḍārabah tidak 100% diberikan Nasabah sebagai pengelola modal dan penetapan keuntungan di awal akad tanpa melihat nasabah untung atau rugi.